Cover Picture: Development and Characterization of High‐Performance Sodium‐Ion Cells based on Layered Oxide and Hard Carbon (ChemElectroChem 7/2016). Issue 7 (27th June 2016) - Keller, Marlou; Vaalma, Christoph; Buchholz, Daniel; Passerini, Stefano
Abstract : The Front Cover picture illustrates that the development of sodium‐ion cells with good overall electrochemical performance is crucial for successful application in the power grid of the future. More information can be found in the Full Paper by D. Buchholz, S. Passerini, and co‐workers onpage 1124 in Issue 7, 2016 (DOI:10.1002/celc.201600152 ).